1994
DOI: 10.1016/0304-3959(94)90083-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural pain-related disorders and contribution of the saphenous nerve in crush and chronic constriction injury of the rat sciatic nerve

Abstract: This study evaluated the pain-related behaviours induced by 2 models of peripheral sciatic nerve injuries in the rat: transient nerve crush and chronic constriction injury (CCI). Various lesions of the saphenous nerve were performed in order to investigate the role of saphenous innervation in behavioural disorders induced by these nerve injuries. Behavioural testing included assessment of responses to phasic stimulation (mechanical and thermal) and observation of 'spontaneous' pain-related behaviour. Results c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 30 publications
2
33
0
1
Order By: Relevance
“…The motor function recovery of sciatic nerve in this study was in agreement with the previous study which had reported that the motor function recovery in the foot showed fully recovery after sciatic nerve crush injury within 3 weeks (Vogelaar et al, 2004). It has been reported that after nerve crush injury, the neuropathic pain which manifested as allodynia has been developed within the first 3 weeks (Attal et al, 1994;Kingery et al, 1994;Przewlocki et al, 1999;Vogelaar et al, 2004). Thus, the slow recovery process of the sensory nerve observed in this study may occur partly due to the development of neuropathic pain which takes much longer to resolve.…”
Section: Discussionsupporting
confidence: 92%
“…The motor function recovery of sciatic nerve in this study was in agreement with the previous study which had reported that the motor function recovery in the foot showed fully recovery after sciatic nerve crush injury within 3 weeks (Vogelaar et al, 2004). It has been reported that after nerve crush injury, the neuropathic pain which manifested as allodynia has been developed within the first 3 weeks (Attal et al, 1994;Kingery et al, 1994;Przewlocki et al, 1999;Vogelaar et al, 2004). Thus, the slow recovery process of the sensory nerve observed in this study may occur partly due to the development of neuropathic pain which takes much longer to resolve.…”
Section: Discussionsupporting
confidence: 92%
“…11 Reports of bilateral hind paw hyperalgesia after unilateral injury demonstrate that contralesional changes affect behavior. 12,13 Systemic lidocaine has different effects against the hyperalgesia that develops in the paws ipsi-lateral and contralateral to nerve ligation.…”
mentioning
confidence: 99%
“…sectioned nerve. Such autotomy has been observed after complete sciatic section, 14 crush, 15 or cryolesions (transient freezing). 16 Trunk lesions have been observed to produce such autotomy in several species.…”
Section: Nerve Sectionmentioning
confidence: 95%